IMPROVING BEGINNING CALCULATING ABILITY THROUGH MODIFIED COGGLAK MEDIA IN CHILDREN AGED 4-5 YEARS - Pratistiningtyas, Mittha; Rakhmawati, Nur Ika Sari (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Researchers will conduct this research aiming to improve the numeracy skills of children aged 4-5 years through the media of saving corn at Pembina II Sooko Public Kindergarten, Mojokerto. This study used the Classroom Action Research (CAR) method which was carried out using two cycles of action. The subjects of this study were 26 children from Group A1 of TK Negeri Pembina II Sooko. Data collection techniques through observation, interviews, and documentation. The results showed that there was an increase in the numeracy skills of children aged 4-5 years through the